Communication behavior and entrepreneurial traits of micro-entrepreneurs in Malaybalay City, Philippines - Cabrera, Liza A. (The Philippine Journal of Development Communication, 2010)
Entrepreneurs are known to have unique entrepreneurial traits, yet not much is known about how they communicate. This study dealt with the communication behavior of micro-entrepreneurs in Malaybalay City. It focused on information needs, information seeking and utilization behaviors, and information expenditure. A survey was conducted among randomly selected Department of Trade and Industry-registered micro-enterprise owners. Frequencies, percentages, correlation, and chi-square statistics were used to draw the analyses and test the stated hypothesis.